(3GdfXQjI h JWHjbGJgGs - (3NGdO eMeO(B, (3GdShGYjs ((3GQHO(B:s (3YGde GdcJH GdMOjK(B,s, 2010)
(3YGde GdEbJUGO GdOhdj(B- (3COhGJ JMdjd feGPL GdJLGQI GdOhdjI(B- (3EfJGLjI GdYed hGdeRGjG GdfSHjI (B((3fehPL QjcGQOh(B)- (3GdJLGQI hJhRjY GdONd GdeMdj(B((3fehPL GdYhGed GdfhYjI(B)- (3GdfehPL GdeYjGQj ddJLGQI GdOhdjI(B- (3haQI YfGUQ GdEfJGL(B((3fehPL gcTQ(B-(3Chdjf(B)- (3JWhQGJ fXQjI GdJLGQI GdOhdjI(B- (3Gdfeh GdEbJUGOj hGdJLGQI GdOhdjI(B- (3GdJLGQI GdOhdjI hGdJfejI GdEbJUGOjI(B- (3MQcI YfGUQ GdEfJGL GdOhdjI(B.s
(3eQGLY U(B.305s
Keywords: (3GdGbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdOhdjIs